Lesions of the Intergeniculate Leaflet Lead to a Reorganization in Circadian Regulation and a Reversal in Masking Responses to Photic Stimuli in the Nile Grass Rat - Gall, Andrew J. (Public Library of Science, 2013)
Light influences the daily patterning of behavior by entraining circadian rhythms and through its acute effects on activity levels (masking). Mechanisms of entrainment are quite similar across species, but masking can be very different. Specifically, in diurnal species, light generally increases locomotor activity (positive masking), and in nocturnal ones, it generally suppresses it (negative masking). The intergeniculate leaflet (IGL), a subdivision of the lateral geniculate complex, receives direct retinal input and is reciprocally connected with the primary circadian clock, the suprachiasmatic nucleus (SCN). Here, we evaluated the influence of the IGL on masking and the circadian system in a diurnal rodent, the Nile grass rat (Arvicanthis niloticus), by determining the effects of bilateral IGL lesions on general activity under different lighting conditions. To examine masking responses, light or dark pulses were delivered in the dark or light phase, respectively. Light pulses at Zeitgeber time (ZT) 14 increased activity in control animals but decreased it in animals with IGL lesions. Dark pulses had no effect on controls, but significantly increased activity in lesioned animals at ZT0. Lesions also significantly increased activity, primarily during the dark phase of a 12:12 light/dark cycle, and during the subjective night when animals were kept in constant conditions. Taken together, our results suggest that the IGL plays a vital role in the maintenance of both the species-typical masking responses to light, and the circadian contribution to diurnality in grass rats.